2021
DOI: 10.1016/j.jse.2020.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Do patient outcomes and follow-up completion rates after shoulder arthroplasty differ based on insurance payor?

Abstract: Background: Disparities associated with socioeconomic status (SES) and insurance coverage have been shown to affect outcomes in different medical conditions and surgical procedures. We hypothesized that patients insured by Medicaid will be associated with lower follow-up rates and inferior outcomes relative to those with Medicare or private insurance. Methods: Patients undergoing shoulder arthroplasty, including anatomic total shoulder arthroplasty, reverse arthroplasty, and hemiarthroplasty, were enrolled pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“… 22 , 23 , 24 , 25 More specifically, recent investigations have demonstrated that in those undergoing total joint arthroplasty of the hip, knee, or shoulder, patients with Medicaid have greater resource use, greater complication rates, and poorer postoperative outcomes. 8 , 10 , 13 , 14 , 23 , 26 , 27 With the expansion of Medicaid through the Affordable Care Act in 2014, the investigation of these disparities in one of the most common orthopaedic sports medicine procedures performed, ACL reconstruction, is critical. 23 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 22 , 23 , 24 , 25 More specifically, recent investigations have demonstrated that in those undergoing total joint arthroplasty of the hip, knee, or shoulder, patients with Medicaid have greater resource use, greater complication rates, and poorer postoperative outcomes. 8 , 10 , 13 , 14 , 23 , 26 , 27 With the expansion of Medicaid through the Affordable Care Act in 2014, the investigation of these disparities in one of the most common orthopaedic sports medicine procedures performed, ACL reconstruction, is critical. 23 …”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the greater difficulty patients with Medicaid insurance face when trying to access PT appointments. 13 For instance, a cross-sectional study conducted in a large metropolitan area within a Medicaid-expansion state found that 43% fewer PT clinics accept Medicaid and those patients with Medicaid must wait significantly longer for an initial appointment as compared with private insurance patients. 28 The PT benefits covered by Medicaid insurance in 2 different states (Illinois and Indiana) is provided in Table 5 , suggesting there is no barrier to accessing PT for patients with Medicaid insurance with regards to limitations on number of PT visits or other restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations